Nothing matters: the significance of the unidentifiable, the superficial and nonsense - Tore Dag Bøe; Inger Beate Larsen; Alain Topor (International Journal of Qualitative Studies on Health & Well-Being, 2019)
Purpose: The aim of this study is to explore the ways in which “small things” may be of importance for people with mental health difficulties. Method: Empirical material from three different studies was reanalysed through a phenomenological, dialogical, approach. Results: We discovered some paradoxical aspects of small things: i.e., they could be about “something” that was difficult or even impossible to identify. The unidentifiable could be about bodily, sensual experiences that are superficial (i.e., belonging to the surface). The interaction with others highlighted as significant could be about doing something fun, talking nonsense or kidding around, and hence not at all about making sense of something—a kind of important nonsense. We summarize these aspects in three themes: the importance of the unidentifiable, the superficial and nonsense. These aspects can be regarded as small things—even “nothings”—that make it possible “to stay in the world”. Conclusion: We elaborate on the findings in relation to the following: Gumbrecht’s critique of the prevailing hermeneutic world-view with its idea that “interpretation is humankind’s exclusive way of relating to the world”, Ingold’s idea that social life is lived in relations of “interfacility” and hence a turn to surfaces is needed for a “restoration of social life”, and Biesta’s idea of existence as “coming into the world in the presence of others”.